1995
DOI: 10.1074/jbc.270.31.18660
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation and Activation of β-Adrenergic Receptor Kinase by Protein Kinase C

Abstract: The aim of this study was to test the possible modification of beta-adrenergic receptor kinase (beta ARK) activity by second messengers and/or their downstream components. Using human mononuclear leukocytes (MNL), we found that calcium ionophores could elevate beta ARK activity by about 80% in a protein kinase C (PKC)-dependent manner. This was confirmed by the ability of the PKC activator phorbol 12-myristate 13-acetate (PMA) to produce a similar effect, suggesting a PKC-dependent modulation of beta ARK activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
126
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 32 publications
10
126
4
Order By: Relevance
“…These results are opposite to the previously reported roles of PKCs on the homologous regulatory processes of GPCRs [8,10]. We conducted more systemic subsequent studies to outline a novel pathway that is involved in the PKC-mediated inhibition of homologous regulatory pathways of GPCRs.…”
Section: Introductioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These results are opposite to the previously reported roles of PKCs on the homologous regulatory processes of GPCRs [8,10]. We conducted more systemic subsequent studies to outline a novel pathway that is involved in the PKC-mediated inhibition of homologous regulatory pathways of GPCRs.…”
Section: Introductioncontrasting
confidence: 55%
“…For example, the enzymatic activities of GRK2 were shown to be increased through phosphorylation on the 29th serine residue by PKCa, c, and d in vitro [8]. Subsequent studies suggested that PKC activates GRK2 by enhancing its translocation to the plasma membrane [9,10]. On the other hand, some studies have shown that PKCs phosphorylate Raf kinase inhibitor protein (RKIP), which in turn inhibits GRK2 activities [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, involvement of arrestins in GPCR internalization in the absence of receptor phosphorylation has been reported (63,64). In the case of CXCR4, phosphorylation could occur by several mechanisms, such as SDF-1␣-mediated receptor activation and phosphorylation by GRKs, direct phosphorylation of receptor by protein kinase C as a result of phorbol ester stimulation, or phosphorylation by GRK2 as a result of its activation via phorbol ester-mediated activation of protein kinase C (54,55). The serines at positions 344, 346, 347, and 348 are potentially good candidates for phosphorylation by GRK2, since they are Cterminal to an acidic residue (65).…”
Section: Fig 6 Mutagenesis Of the Cxcr4 C-tailmentioning
confidence: 99%
“…GRK2 (54,55). We cotransfected HEK-293 cells with CXCR4 and dynamin-K44A, two different arrestin-3 dominant negative mutants and a dominant negative mutant of GRK2.…”
Section: Fig 2 Pma-and Rantes-mediated Ccr5 Internalizationmentioning
confidence: 99%
“…Protein kinase C-mediated phosphorylation increases membrane association (Chuang et al, 1995;Winstel et al, 1996) GRK3 bARK2 ENSG00000100077 b-Adrenergic receptor kinase 2, ADRBK2 -…”
Section: Anaphylatoxinmentioning
confidence: 99%